(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2022)
Purpose: The aim of this paper is to examine empirically the relationship between liquidity management and profitability of Croatian small and medium enterprises in trade and to provide empirical evidence of the effects of liquidity management on the level of profitability during the COVID-19 crisis. Methodology: The analysis began with descriptive statistics, where the authors observed the following variables: ROA, current liquidity, accelerated liquidity, immediate liquidity and employment. The collected data analyzed descriptive statistics and compared the Wilcoxon signed-rank test. The authors made six regression models and performed regression diagnostics for all models. The problem of heteroscedasticity examined the Breusch-Pagan test, the normality of relation errors examined the Jarque-Bera test, while multi-collinearity examined the variance inflation factor (VIF). Results: All six models confirmed a statistically significant and positive impact of liquidity on the level of profitability in both years, which means that the increase in liquidity will result in an increase in the level of profitability of the observed companies. Control variables of company size and trade category did not prove statistically significant. Conclusion: Scientific contribution is the development of a model for the analysis of the impact of liquidity on the profitability for small and medium enterprises in trade. The model is also applicable to similar transition and post-transition economies, especially to those in the region that have similar economic development as it will help economic policy makers and corporate managers understand the importance of the impact of liquidity on profitability levels.